Exponential stability of random impulsive pantograph equations. (4th February 2021) - Vinodkumar, A.; Senthilkumar, T.; Liu, Zhongmin; Li, Xiaodi
Abstract : In this paper, we study the p th moment exponential stable and p th moment weakly exponential stable results for the random impulsive pantograph delay differential equations (RIPDDEs). Further, we obtained some sufficient conditions by using the method of Lyapunov and Razumukhin technique. Finally, we give several numerical examples with their simulations are provided to illustrate the effectiveness of the proposed results.